A Review of Research on Technology-Supported Language Learning and 21st Century Skills - Rustam Shadiev; Xun Wang (Frontiers in Psychology, 2022)
Modern society needs people to be equipped with 21st century skills (e.g., critical thinking, creativity, communication, digital literacy, or collaboration skills). For this reason, teaching and learning nowadays should promote not only students' knowledge acquisition in various learning contexts but also their 21st century skills, and language learning context is no exception. This study reviewed research on technology-supported language learning and 21st century skills. The reason is that earlier studies reviewed only articles related to language learning supported by technology and mostly focused on languages, language skills and technologies used. That is to say, 21st century skills were not considered in earlier review studies. The present study selected and reviewed 34 articles published between 2011 and 2022 (February) and focused on the following dimensions: (1) research focus such as language skills and 21st century skills; (2) theoretical foundations; (3) technologies; (4) learning activities; (5) methodology; and (6) findings. The present research found that reviewed studies had focused most frequently on such language skills as speaking and writing and on such 21st century skills as communication and collaboration. The social constructivism theory was often used by scholars to base their studies on. Facebook, Google Docs, and Moodle were popular technologies in reviewed studies to facilitate language and 21st century skills. Scholars in reviewed studies reported that technology-supported language learning activities provided learners with good learning experiences and enhanced their learning motivation, engagement, and confidence. However, some challenges that learners faced during learning activities were also reported. Based on the results of the review, this study made several recommendations for stakeholders such as educators and researchers in the field.